Temporal Petal Closure Benefits Reproductive Development of Magnolia denudata (Magnoliaceae) in Early Spring - Liu, Liya; Zhang, Chulan; Ji, Xiangyu; Zhang, Zhixiang; Wang, Ruohan (Frontiers in Plant Science, 2017)
The Magnoliaceae shows strong phylogenetic niche conservatism, in which temporal petal closure has been extensively reported. However, it is yet elusive whether temporal petal closure is an idle floral character inherited from their ancestors or an adaptive trait to their habitats. Here, we monitored the process of temporal floral closure and re-opening in a thermogenic plant, Magnolia denudata (Magnoliaceae). Furthermore, we artificially interrupted temporal petal closure and investigated its effects on development of female and male gametophytes. Intriguingly, we found considerable anatomical changes in the anthers shortly after temporal closure of petals: disintegration of tapeta, crack of anther walls, and release of matured pollens. In comparison with normal flowers, artificially interrupted flowers (no petal closure) showed delayed anther development and slower pollen germination on stigmas, while little difference in embryo morphology was observed during the early stage of embryo development. Moreover, seed set and quality were significantly decreased when petal closure was prevented. In addition, we found pollination accelerated floral closure in M. denudata. Taken together, temporal floral closure benefits reproduction of M. denudata in early spring by promoting anther development and pollen function, which suggests that it is an adaptive floral trait to its specific habitat.